Digital Promotion Strategy: An Analysis of Scarlett Whitening's Increased Sales Through Instagram - Maharani, Amanda; Abidin, Zaenal; Kadarsih, Sri (Zabags International Journal of Economy, 2025)
This study aims to analyze the promotional strategies implemented by Scarlett Whitening in increasing product sales through the Instagram platform. With the increasing use of social media, digital promotion has become a key in modern marketing strategies, especially in the beauty industry. The research method used is a descriptive qualitative approach with data collection techniques in the form of interviews with store owners, consumers, and direct observation of Scarlett Whitening's Instagram account. The results of the study show that promotional strategies such as celebrity endorsements, giveaways, attractive visual content, and active interaction on social media are proven to be able to increase brand awareness and have a significant impact on increasing product sales. Consistent and adaptive promotion to social media trends is an important factor in Scarlett Whitening's marketing success.